Engaging Canadians in evidence-based communication about vaccines: a scoping review protocol of immunisation support programs in Canada. Issue 4 (21st April 2022) - Kelly, Katherine Jennifer; Mears, Kim; Burns, Margie; Montelpare, William
Abstract : Objective: To identify, characterise and map the existing knowledge about (1) immunisation programmes that provide evidence-based support about vaccines to Canadians and reduce barriers to vaccination; and (2) barriers and facilitators to the delivery of immunisation support programmes. Introduction: Vaccine hesitancy is a complex issue that has significant repercussions for the health and safety of Canadians. Engaging in evidence-based communication about vaccines can reduce vaccine hesitancy and increase participation in immunisation programmes. Methods: The Joanna Briggs Institute methodology for scoping reviews will be used for this scoping review. A comprehensive keyword search strategy was developed and translated for six electronic databases on 19 November 2021: CINAHL via EBSCOhost, APA PsycINFO via EBSCOhost, Academic Search Complete via EBSCOhost, Scopus, Medline via EBSCOhost and EmCare via Ovid. We will identify unpublished literature by searching websites listed in CADTH's Grey Matters checklist and other relevant sources in January 2022. Two independent raters will screen and extract data from identified material. Data will be presented in a tabular form. Inclusion criteria: We will consider Canadian programmes that target the general public and exclude papers targeting health professionals. Our review will not limit by vaccine type and will consider any intervention that aims to inform individuals about immunisation. Our primary concept involves mapping the characteristics of programmes (eg, programme description, delivery format) and our secondary concept will examine barriers and facilitators to programme delivery. Ethics and dissemination: Ethical approval is not required as this study is a review of the published and publicly reported literature. Findings from this review will be disseminated to academic and health system stakeholders to inform immunisation programmes across a wide range of vaccine types and settings. We intend to use the results of this review to develop an immunisation support programme in Prince Edward Island, Canada.